2001
DOI: 10.1046/j.1523-1755.2001.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1,25(OH)2D3 in experimental mesangial proliferative nephritis in rats

Abstract: 1,25(OH)2D3 can reduce glomerular hypercellularity, inflammatory infiltration in anti-Thy-1.1 nephritis, preserving the apoptotic response of the reparative phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 25 publications
7
81
1
1
Order By: Relevance
“…7,23 Animal studies have shown that elevated levels of active vitamin D contribute to factors that are hypothesized to be associated with a reduction of kidney disease progression, including reduction in proteinuria, decrease in TGF-b, inhibition of mesangial cell proliferation, and preservation of the structural integrity of glomerular podocytes. [24][25][26][27] Finally, FGF-23 might directly contribute to kidney injury, similar to the direct effect of FGF-23 on cardiac myocytes. 9 Previous studies suggest that FGF-23 elevation precedes abnormalities in other mineral metabolism markers, which supports the potential role of FGF-23 as an early indicator of renal pathology.…”
Section: Discussionmentioning
confidence: 94%
“…7,23 Animal studies have shown that elevated levels of active vitamin D contribute to factors that are hypothesized to be associated with a reduction of kidney disease progression, including reduction in proteinuria, decrease in TGF-b, inhibition of mesangial cell proliferation, and preservation of the structural integrity of glomerular podocytes. [24][25][26][27] Finally, FGF-23 might directly contribute to kidney injury, similar to the direct effect of FGF-23 on cardiac myocytes. 9 Previous studies suggest that FGF-23 elevation precedes abnormalities in other mineral metabolism markers, which supports the potential role of FGF-23 as an early indicator of renal pathology.…”
Section: Discussionmentioning
confidence: 94%
“…6,18 In animal models of primary glomerular diseases, administration of vitamin D reduces glomerular infiltration of inflammatory cells. 6,9 Consistently, a decreased inflammation is associated with higher serum vitamin D level in patients with CKD. 19 Vitamin D may exert its immunomodulatory action through regulating the activity of many types of immune cells such as macrophages, dendritic cells, and T cells.…”
mentioning
confidence: 87%
“…[3][4][5] Evidence is also mounting that vitamin D analogue is renoprotective in different experimental nephropathies. 6 Although early studies largely focused on primary glomerular diseases, [7][8][9] active vitamin D was shown to display beneficial effects in obstructive nephropathy, 10 a model characterized by inflammatory infiltration, tubular atrophy, and interstitial fibrosis. The therapeutic effects of active vitamin D in obstructive nephropathy are thought to be mediated by its ability to preserve tubular epithelial integrity via inhibiting epithelial-to-mesenchymal transition (EMT) 10 ; however, in view of its pleiotropic property, it is conceivable that vitamin D could elicit its renoprotection by a multitude of actions.…”
mentioning
confidence: 99%
“…Panichi et al [19] investigated the role of 1,25-(OH) 2 D 3 in a rat model with mesangial nephritis, and found that 1,25-(OH) 2 D 3 treatment reduced IL-6 cytokine, macrophage infiltration, apoptosis. They also demonstrated its antiproliferative effect by attenuating immunolabeling to proliferating cell nuclear antigen (PCNA), as well as its anti-inflammatory activities and effects on cell differentiation, proliferation and apoptosis [19].…”
Section: Vitamin D In Inflammationmentioning
confidence: 99%
“…They also demonstrated its antiproliferative effect by attenuating immunolabeling to proliferating cell nuclear antigen (PCNA), as well as its anti-inflammatory activities and effects on cell differentiation, proliferation and apoptosis [19].…”
Section: Vitamin D In Inflammationmentioning
confidence: 99%